THE FACTORS CONTRIBUTING TO THE STUDENTS' WRITING ANXIETY AT THE UNIVERSITY LEVEL - Siti Istiqomah; Silih Warni; Zuhad Ahmad (Prosiding Seminar Nasional Berseri, 2020)
This study aims at investigating the factors contributing to the students’ writing anxiety at the university level. A total of 205 students majoring in English Education Department and English Literature have participated in this study. Second Language Writing Anxiety Inventory (SLWAI) and Causes of Writing Anxiety Inventory (CWAI) developed by Cheng (2004) were adapted in this study for the data collection. The writer used mixed method (qualitative and quantitative). Interviews were conducted in addition to the questionnaire. The questionnaire used a close question, while the interview used open-ended questions. The questionnaires were given to 205 students, but only seven students were interviewed purposively. Finally, based on the findings, there were four main types found as the factors contributing the students’ writing anxiety namely, low self-confidence in writing (40.63%), fear of writing test (26.70%), fear of teacher’s negative evaluation (17.96%), and lack of interest in writing (14.71%). The result also highlighted that students who study foreign languages at the university level still feel anxiety in writing. The percentage results obtained from each factor indicate the level of anxiety felt. This was found from what they had filled out in the questionnaire and was strengthened by the answers from the interview session.